Gastrointestinal fistulas: An Update - Moniruddin, ABM; Chowdhury, Salma; Sharif, Md Sayeed Bin; Rahman, Md Masudar; Faisal, M Fardil Hossain; Hasan, Tanvirul; Khan, Md Rashed (KYAMC Journal, 2018)
A gastrointestinal (GI) fistula is an abnormal connection between gut (GI tract) and an epithelialized surface of skin or another hollow organ or another part of gut. These GI fistulas can cause profound GI bleeding, which may need emergency surgery. Other complications include Malnutrion, Undernutrion, Anaemias, Fluid, and Electrlyte imbalances, Hypovolemic shock, Septic shock, Pyaemic abscesses, Kidney malfunction and failure, Cardiac dysrhythmias, and failure, Hepatitis, Cerebral dysfynction and strokes, DIC etc if neglected, maltreated or untreated. Most GI fistulas occur as a complication of abdominal surgery. However, some fistulas evolve spontaneously and are usually the result of intra-abdominal inflammation or infection. Several classification systems for GI fistulas exist, none of which are used exclusively. The most commonly used classification systems are based on anatomic, physiologic (output volume), and etiologic characteristics. Used in combination, these classifications can help to provide an integrated understanding and optimal management scheme for the fistula. History taking, Physical examination, Endoscopy, Imaging studies and other laboratory tests are variably required for total assessment, evaluation, and concrete diagnosis. Intensive medical, and surgical therapies are now quite dramatically helpful to reduce the morbidity and mortality. This treatise on GI fistula is here to update the information about the latest developments of GI fistula. KYAMC Journal Vol. 9, No.-2, July 2018, Page 87-94